2019
DOI: 10.1021/acs.inorgchem.9b02530
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence for Electronic Control of Heme Hydroxylation by IsdG

Abstract: Staphylococcus aureus IsdG catalyzes a unique trioxygenation of heme to staphylobilin, and the data presented in this article elucidate the mechanism of the novel chemical transformation. More specifically, the roles of the second-sphere Asn and Trp residues in the monooxygenation of ferric− peroxoheme have been clarified via spectroscopic characterization of the ferric−azidoheme analogue. Analysis of UV/vis absorption data quantified the strength of the hydrogen bond that exists between the Asn7 side chain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 64 publications
(215 reference statements)
5
34
0
Order By: Relevance
“…10 Instead, the monooxygenation rate enhancement is likely derived from an electronic structure change similar to that previously reported for IsdG. 32 These data elucidate a mechanism where a dynamic equilibrium between planar and ruffled heme exists within the MhuD active site, 12 but heme monooxygenation only proceeds for the ruffled conformation.…”
Section: Discussionsupporting
confidence: 72%
“…10 Instead, the monooxygenation rate enhancement is likely derived from an electronic structure change similar to that previously reported for IsdG. 32 These data elucidate a mechanism where a dynamic equilibrium between planar and ruffled heme exists within the MhuD active site, 12 but heme monooxygenation only proceeds for the ruffled conformation.…”
Section: Discussionsupporting
confidence: 72%
“…10 Instead, the monooxygenation rate enhancement is likely derived from an electronic structure change similar to that previously reported for IsdG. 32 These data elucidate a mechanism where a dynamic equilibrium between planar and ruffled haem exists within the MhuD active site, 12 but haem monooxygenation only proceeds for the ruffled conformation.…”
Section: A Proposed Mechanism For Haem Oxygenation By Mhudsupporting
confidence: 72%
“…5 An X-ray crystal structure for WT IsdG-heme-CN is not available, but heme ruffling in WT IsdG-heme-CN has been estimated to be 2.0 Å based upon spectroscopically-validated QM/MM calculations. 7 The UV/Vis Abs spectra of WT and W67F IsdG-heme-CN are quite similar (Figure 3), but closer inspection reveals that the W67F substitution blueshifts both the Q and Soret bands by 100 cm -1 . Based upon the QM/MM structure of WT IsdG-heme-CN, the UV/Vis Abs spectra of WT and W67F IsdG-heme-CN, and the established ruffling model noted above, the magnitude of heme ruffling in W67F IsdG-heme-CN was estimated to be 1.7 Å.…”
Section: Figurementioning
confidence: 92%
“…6 Most recently, spectroscopically-validated hybrid quantum mechanics/molecular mechanics (QM/MM) calculations suggested that S. aureus IsdG, a third non-canonical heme oxygenase, induces an intermediate degree of heme ruffling compared to IsdI and MhuD (Figure 1). 7 The observation of two distinct heme conformations within the MhuD active site is fairly unique within the heme protein literature, and the possibility that IsdG and IsdI also stabilize two distinct heme substrate conformations had not been evaluated prior to this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation